Physiological and proteomic analysis of halophyte Halogeton glomeratus in response to Ni2+ stress - Yao, Lirong; He, Jianjun; Wang, Juncheng; Li, Baochun; Meng, Yaxiong; Ma, Xiaole; Si, Erjing; Zhang, Hong; Yang, Ke; Wang, Huajun (Frontiers in Plant Science, 2026)
Halogeton glomeratus (H. glomeratus) is a halophyte that can remediate heavy metals in soil. However, knowledge regarding the mechanisms of Ni remediation in H. glomeratus is limited. In this study, the physiological and molecular mechanisms of H. glomeratus seedlings exposed to different Ni2+ conditions were investigated. The results revealed that H. glomeratus growth was significantly inhibited when the Ni2+ concentration was higher than 1.5 mM, but the seedlings did not experience any seedling death and physiological characteristics showed no significant decrease. The accumulation of Ni2+ in H. glomeratus was found in Ni2+-treated seedling roots, stems and leaves. The size of water-storage tissue, the thickness of cortex and the number of large parenchyma cell rose in H. glomeratus with the increasing of Ni2+ concentrations. Under the 1.5 mmol/L Ni2+ for 6 h, 12 h, 24 h, and 48 h, the number of increased abundant proteins was higher than that of decreased abundant proteins at each time point, and numerous differentially abundant proteins mainly involved in response to transmembrane transport, oxidative stress and metabolic process. More importantly, we obtained 36 detoxification-related proteins with increased abundance that were related to Ni2+ stress, which were located in apoplast, plasma membrane, vacuolar membrane, chloroplast, and mitochondria, respectively. These biological processes and mechanisms synergistically regulated the Ni2+ tolerance in H. glomeratus, providing new insights into the application of phytoremediation using wild genetic resources such as halophyte H. glomeratus.